Osteogenic effects of microRNA-335-5p/lipidoid nanoparticles coated on titanium surface. (September 2021) - Wang, Qiang; Wang, Xiaoying; Valverde, Paloma; Murray, Dana; Dard, Michel M.; Van Dyke, Thomas; Xu, Qiaobing; Xu, Xin; Karimbux, Nadeem; Tu, Qisheng; Chen, Jake
Highlights: MicroRNA-335-5p/lipidoid nanoparticles exhibit high cell transfection efficiency. MicroRNA-335-5p/lipidoid nanoparticles sustain stability on the implant surface. MicroRNA-335-5p/lipidoid nanoparticles promote osteogenic differentiation. This nano-complex could be used to enhance implant osseointegration. Abstract: Objective: In this study, we aimed to investigate the therapeutic potential of miR-335-5p lipidoid nanocomplexes coated on Titanium (Ti) SLActive surface by lyophilization. Design: In our model, we coated miR-335-5p/Lipidoid nanoparticles on titanium implant, seeded GFP-labelled mouse bone marrow stromal cells (BMSCs) onto the functionalized Ti implant surface, and analyzed the transfection efficiency, cell adhesion, proliferation, and osteogenic activity of the bone-implant interface. Results: The Ti SLActive surface displayed a suitable hydrophilicity ability and provided a large surface area for miRNA loading, enabling spatial retention of the miRNAs within the nanopores until cellular delivery. We demonstrated a high transfection efficiency of miR-335-5p lipidoid nanoparticles in BMSCs seeded onto the Ti SLActive surface, even after 14 days. Alkaline phosphatase (ALP) activity and cell vitality were significantly increased in BMSCs transfected with miR-335-5p at 7 and 14 days as opposed to cells transfected with negative controls. When miR-335-5p transfected BMSCs were induced to undergo osteogenic differentiation, we detected increased mRNA expression of osteogenic markers including Alkaline phosphatase (ALP), collagen I (COL1), osteocalcin (OCN) and bone sialoprotein (BSP) at 7 and 14 days as compared with negative controls. Conclusion: MiR-335-5p lipidoid nanoparticles could be used as a new cost-effective methodology to increase the osteogenic capacity of biomedical Ti implants.